2019
DOI: 10.1097/md.0000000000016543
|View full text |Cite|
|
Sign up to set email alerts
|

Association between CYP1A1 rs4646903 T > C genetic variations and male infertility risk

Abstract: Background: Number of studies have been performed to investigate the relationship between the CYP1A1 rs4646903 polymorphism and male infertility risk, but the sample size was small and the results were conflicting. A meta-analysis was performed to assess these associations. Methods: A systematic search was conducted to identify all relevant studies from Medline, Web of science, Embase, China biology medical literature database (CBM), China Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Nejati et al [21] have conducted a meta-analysis and have indicated that, CYP1A1 3801T > C transition can be considered as a biomarker for risk of male infertility within Asian populations. Cao et al [22] have similarly investigated the relationship between the studied polymorphism and male infertility risk and came to the conclusion that this variant can play a role in individual susceptibility to male infertility in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Nejati et al [21] have conducted a meta-analysis and have indicated that, CYP1A1 3801T > C transition can be considered as a biomarker for risk of male infertility within Asian populations. Cao et al [22] have similarly investigated the relationship between the studied polymorphism and male infertility risk and came to the conclusion that this variant can play a role in individual susceptibility to male infertility in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Inability to achieve clinical conception despite 1 year of unprotected intercourse with the same partner is categorized as human infertility by the World Health Organization (WHO) (Zhao et al, 2016;Buhling et al, 2019;Cao et al, 2019;Hosseini et al, 2019;Wang et al, 2020). A total of 15% (48.5 million) couples worldwide are affected by any kind of infertility, and male infertility dominates the trend with 70% of all cases.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 15% (48.5 million) couples worldwide are affected by any kind of infertility, and male infertility dominates the trend with 70% of all cases. Higher male infertility rates are seen in the population of Central Europe, Eastern Europe, and Africa (Zhao et al, 2016;Buhling et al, 2019;Cao et al, 2019;Hosseini et al, 2019;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the article, “Association between CYP1A1 rs4646903 T > C genetic variations and male infertility risk: A meta-analysis”, [1] which appears in Volume 98, Issue 31 of Medicine Dr. DongLiang Lu's degree should appear as MD and affiliation a. Dr. Qiang Wei's degree should appear as MD.…”
mentioning
confidence: 99%